MENINGKATKAN HASILBELAJAR PASSING ATAS BOLA VOLI MENGGUNAKAN METODE PERMAINAN PADA SISWA KELAS IX.1 SMP ISLAM NURUL IMAN LABUHAN MARINGGAI - Rofiatul Azizah, Listiana; Zulkarnain, Ferdi; Alim Saputra Hidayat, Tri (EDU AKOMMEDIA : JURNAL ILMU PENDIDIKAN, 2025)
The aim of this study is to improve the skill of overhead passing in volleyball The aim of this study is to improve volleyball skills, specifically the overhand passing technique, by implementing the game-based method, so that the learning process can be successful. The method used in this study is action research. Action research aims to improve methods, processes, content, competencies, and learning situations. Prior to the implementation of the game-based method, the students of class IX.1 SMP Islam Nurul Iman Labuhan Maringgai had not reached the expected level of mastery, with only 27% of students achieving success. This was due to many students not mastering the overhand passing technique and not receiving instruction using the game-based method. The results of the study indicate that in Cycle I, the highest score achieved was 89, the lowest was 56, and the average score was 77.15. A total of 17 students, or 65%, achieved mastery. In Cycle II, the highest score was 89, the lowest was 67, and the average score reached 80.53. The percentage of students who achieved mastery increased to 85%, with 22 students successfully completing the task. The overhand passing skills of the students met the success indicator of 80%. Based on these findings, it can be concluded that the use of the game-based method can improve the learning outcomes of overhand passing in volleyball for the students of class IX.1 SMP Islam Nurul Iman Labuhan Maringgai. Therefore, it is recommended that the game-based method be applied to help students overcome difficulties in learning the overhand passing technique in volleyball, as it has proven to be effective in enhancing learning outcomes.